Knowledge, attitudes and practices related to hepatitis C among gay and bisexual men in the era of direct-acting antivirals: implications for treatment and prevention. Issue 5 (3rd May 2020) - Brener, Loren; Murphy, Dean A.; Ellard, Jeanne; Cama, Elena; Fraser, Neil; Murray, Joel
Abstract: Increases in hepatitis C (HCV) infections among gay and bisexual men have recently been reported in a number of countries, with sexual transmission being the primary route of infection. Given that in countries such as Australia most gay and bisexual men living with HIV are already engaged in clinical care – as are an increasing number of HIV-negative men – there is potential for reducing onward HCV transmission through proactive testing and treatment. This study explored knowledge, attitudes and practices related to HCV among 194 gay and bisexual men collected through an online survey in Australia. Overall, respondents had high levels of HCV knowledge; however, only 76% knew about the availability of new treatments for HCV. Men's knowledge of their own HCV testing history was uncertain, with one in six unaware if they had ever been tested. Among men who reported recent drug injecting, one-third had been injected by someone else, and two-thirds had injected someone else, indicating a subculture of cross-administering within sexualised drug-use networks. We argue that the robust sexual, socio-cultural and clinical infrastructure that has been developed by – and for – gay and bisexual men around HIV care and prevention creates the potential for reducing HCV in this group.